Exploring Secondary School Graduates’ Knowledge and Interest in Nursing Profession: A Study in Arar, Kingdom of Saudi Arabia - Alboelola, Taghreed Hussien; Lopez, Leticia P.; Alruwaili, Karimah Kunaydir; Alruwaili, Jawaher Eid; Garallah, Reem Eesa; Alrowily, Amani Helal; Ayed, Manal Mohamed Ahmed (Journal of Posthumanism, 2025)
Background: The research aims to assess the knowledge and perceptions of secondary school graduates about the nursing profession in Arar, KSA. Using a structured questionnaire, the study evaluated sources of information, familiarity with nursing duties, career interest, and attitudes towards nursing. Objectives: To evaluate the knowledge, perceptions, and career interest of secondary school graduates concerning the nursing profession. Materials and Methods: A total of 120 students were selected from various secondary schools within the Arar Government. To ensure a representative sample across gender and grade levels, a stratified random sampling method was employed. This target group was chosen as they are in the final years of secondary education and actively considering their career options. The study found that familial influence (48%) and the internet (38%) were the primary sources of information about nursing, while educational settings played a minor role. Despite a high interest in nursing careers (81%), there were gaps in students’ understanding of nursing responsibilities and participation in medical decision-making. The study also examined the factors influencing nursing licensure exam preparation, highlighting a significant correlation between knowledge and examination readiness. Conclusions: In regions like Arar, where limited exposure to the nursing profession exists, these factors play a significant role in shaping students’ career choices. There are several factors that influence the knowledge and interest in nursing among secondary school graduates, including cultural perceptions, educational exposure, societal influences, and family support. Addressing misconceptions, providing better education and career guidance, and showcasing the diverse opportunities within nursing can encourage more students to pursue this essential profession. Future research in this area is critical to developing targeted strategies that promote nursing as a desirable and respected career choice, particularly in smaller cities in Saudi Arabia. The findings underscore the need for targeted educational initiatives to enhance nursing awareness and address career barriers, particularly financial constraints.